Gambling-related suicides and suicidality: A systematic review of qualitative evidence - Marionneau, Virve; Nikkinen, Janne (Frontiers in Psychiatry, 2022)
The relationship between gambling and suicides or suicidality has received much research attention in recent years. Review studies have already mapped the quantitative occurrence of suicide attempts, suicides, and self-harm among gamblers, and found a positive association. Related comorbidities and conditions have also been charted in previous reviews. However, there is still a gap in knowledge regarding the actual processes that connect gambling and suicidal behavior. To understand these processes, the current paper conducts a systematic review of qualitative evidence on gambling-related suicides and suicidality. The aim was to identify the role of gambling as well as of confounding factors in suicidality, and what kind of support suicidal individuals have received or would need. We searched for relevant literature in seven scientific databases. We included all studies that presented empirical qualitative evidence on gambling-related suicide, suicidality and/or self-harm (N = 20). The results show two main processes that connect gambling and suicidal behavior: indebtedness and shame. At the same time, suicide is a multifactorial phenomenon, and related to other confounding factors. These include psychiatric conditions, personality traits, and life conditions. In many cases, these appear to emerge as a consequence of gambling. Treatment for suicidality has been effective in some cases, but indebtedness and shame may also function as barriers to help-seeking. We conclude that effective prevention is needed by adapting a more comprehensive public health approach and population-level interventions.